Effects of MDL 73005EF on central pre- and postsynaptic 5-HT1A receptor function in the rat in vivo. - Gartside, SE; Cowen, P; Hjorth, S (1990)
The effects of MDL 73005EF (8-[2-(2,3-dihydro-1,4-benzodioxin-2-yl)methylamino]-8- azaspiro[4,5]decan-7,9-dione methyl sulphonate), a novel selective 5-HT1A receptor ligand with putative anxiolytic properties, were explored using models of central pre- and postsynaptic 5-HT1A receptor function in the male rat. MDL 73005EF dose dependently decreased the hippocampal 5-HT output measured by in vivo microdialysis in chloral hydrate-anaesthetised rats and this response was antagonised by the 5-HT1A/B receptor antagonist, pindolol. Local administration of MDL 73005EF had no effect on the hippocampal 5-HT output. MDL 73005EF failed to alter basal plasma adrenocorticotropin (ACTH) levels but, in common with pindolol, attenuated the ACTH response to the 5-HT1A receptor agonist, 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT). In contrast to 8-OH-DPAT, MDL 73005EF significantly increased plasma prolactin but apparently not through a 5-HT receptor-mediated mechanism. The results indicate that MDL 73005EF possesses mixed 5-HT1A receptor agonist/antagonist properties, acting as an agonist at presynaptic 5-HT1A receptors controlling 5-HT release and as an antagonist at postsynaptic 5-HT1A receptors mediating ACTH release.